Theoretical-practical interfaces between Continuing Education in Health and Quality of Life at Work (Research, Society and Development, 2020)
The field of worker's health and the quality of life it encompasses promote proposals for strengthening the worker as a subject of knowledge. On the other hand, continuing education aims to mobilize this knowledge. Understanding that both may have important implications, the study aimed to identify theoretical-practical interfaces between “Permanent Education in Health” (PEH) and Quality of Life at Work (QLW) from a program run in the interior of Minas Gerais. The program is a partnership of the federal university with the local SUS network and covers more than 300 workers from 8 municipalities in the health region. This is a qualitative study by thematic content analysis under the reference of the National Policy of Continuing Education. And a quantitative, cross-sectional study to assess QWL using the QWLQ-bref instrument. As a result, the categories were identified: meanings about EPS, subjects involved, ways of doing EPS, challenges to do continuing education, challenges to improve the quality of life of SUS workers and workers and the intertwining of PEH with quality of life . As a result of the application of the questionnaire, an average of 63.77% for QLW was found, understood as satisfactory. It was found that the working conditions and the network structure are significant issues for workers and that permeate both QWL and PEH for this health region. In addition, the power of QVT and PEH as reflection triggers was observed, in order to problematize and strengthen the awareness of the historical subjects involved in SUS.